The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4103/jfmpc.jfmpc_154_19
|View full text |Cite
|
Sign up to set email alerts
|

Medical problem in Asia pacific and ways to solve it: The roles of primary care/family physician (Indonesia Xperience)

Abstract: WHO reported that Environment contributed significantly as the causal of the disease in Asia Pacific. Indonesia is facing major health challenges, namely triple burden health problems, due to communicable diseases, non-communicable diseases and re-emerging disease. Primary care in Indonesia is conducted by Public Health Centers/Puskesmas and Primary Care Clinic covering around 86% of total health care facilities in Indonesia. Primary Care Physician plays important role as a gatekeeper and care coordinator. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…12 While the primary healthcare (PHC) centres are designed as gatekeepers for primary prevention for NCDs, studies have found limited capacity of PHC in proper management of NCDs. 13–15 There is also high public funding allocations to curative services at the hospital-level, 16 with limited investment in preventive and promotive health services. 12 Further, the poor and those living in limited-resource regions have generally lower hospital utilisation due to geographical barriers and high transportation costs.…”
Section: Introductionmentioning
confidence: 99%
“…12 While the primary healthcare (PHC) centres are designed as gatekeepers for primary prevention for NCDs, studies have found limited capacity of PHC in proper management of NCDs. 13–15 There is also high public funding allocations to curative services at the hospital-level, 16 with limited investment in preventive and promotive health services. 12 Further, the poor and those living in limited-resource regions have generally lower hospital utilisation due to geographical barriers and high transportation costs.…”
Section: Introductionmentioning
confidence: 99%
“…8 The P-Care system and the list of diseases should be continuously improved to allow explanation of the GPs' clinical judgement, and primary care accreditation programs initiated by the Indonesian government can also be further applied to upgrade clinical resources rather than focusing on the administration aspects. 34,35 Above all, the Indonesian government is already in an appropriate stage of ensuring affordable and convenient access for people to meet their basic health care needs in primary care. The JKN implementation is relatively recent, and strategies aiming to improve the GP practice would obviously require quite some time.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Indonesia mengalami triple burden masalah kesehatan, yaitu penyakit menular, penyakit tidak menular, dan re-emerging disease. 1 Dari ketiga masalah tersebut, penyakit tidak menular (PTM) menyebabkan lebih banyak kematian dibanding dengan penyakit lain, terdapat 38 juta kematian pada tahun 2012 dan angka ini akan terus bertambah menjadi 52 juta kematian pada tahun 2030. 2 Empat PTM utama adalah penyakit pernapasan kronis, kardiovaskular, kanker, dan diabetes melitus (DM).…”
Section: Pendahuluanunclassified